The gardener of Alcatraz : a true story - Smith, Emma Bland (Charlesbridge, 2022)
"When prisoner Elliott Michener began tending the gardens at Alcatraz, his thoughts of escape were replaced with new skills and a sense of dignity. Back matter discusses the history of Alcatraz and the US prison system today"--